Pengembangan Produk Olahan Singkong Dan Gula Aren Desa Mekarsari Kecamatan Gunungsari - Wuryantoro; Adeel Ahmad Husain; Maradheta Amelia Yupita; Ria Savira; Yessy Kusuma Wati; Azizah Rizkyani; Rahma Khoirunnisa; Lilis Utari; Linda Pratami; Jimmy Areeva Amir van der Kruit; M Andre P Endyaswara; Astami Muzakir; Andhia Rosyantari (Universitas Mataram, 2022)
Abstract: Each region must have assets or potential that can be developed, including Mekar Sari Village, Gunungsari District, West Lombok Regency. One of the assets owned by the people of Mekar Sari Village is cassava and sugar palm plantations. Where the plantation products produce cassava roots and palm sugar. The management is still in the form of intact goods that have not been managed further with a very small selling value. Processed products from cassava roots and palm sugar are numerous and varied. The assistance that will be carried out in this community service activity is the development of processed products from superior raw materials into cassava chips, palm sugar pudding, and palm sugar briquettes. Assistance is provided starting from production, packaging, and marketing. Assistance is carried out on an ongoing basis until the resulting product has a high selling value. This assistance aims to improve the economy, skills, and knowledge of the people of Mekar Sari Village. : Keywords: Cassava Chips, Palm Sugar, Product Marketing